THE STUDY OF EFFICIENCY AND DISCIPLINE ON SHIPMENT FROM WAREHOUSE TO TANJUNG PRIOK PORTThe Study of Efficiency and Discipline on Shipment From Warehouse to Tanjung Priok Port - Miskul Firdaus; Zeinyta Azra Haroen; Deslida Saidah (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2015)
Optimizing the use of land transport with the management of logistics and supply chain management of the warehouse to the port of Tanjung Priok can minimize cost, time, and quantity. Then the delivery of goods is faster,  more focused and more precise. This research uses descriptive quantitative and data is collected from secondary and primary data using SPPSS software 27.00 version. Based on the three proposed research hypotheses, it is proved that the efficiency variable (X1) and variable discipline (X2) --- either individually or together --- have an influence to the shipment of goods from the warehouse in Tangerang to the Port of Tanjung Priok (Y).